Requirements for Reconfiguration Management for Manufacturing Systems. Issue 10 (2022) - Caesar, Birte; Tilbury, Dawn M.; Barton, Kira; Fay, Alexander
Abstract: To remain competitive in a highly dynamic environment, manufacturing companies have to quickly react to disturbances or changing customer requirements. To enable manufacturing systems to cover these dynamics, the concept of reconfigurable manufacturing systems was introduced. From a technical point of view, this concept has been exploited the past 20 years, revealing several different design solutions. However, industrial application is still an exception. Our analysis lead to the assumption that this is due to a lack of operator support for reconfiguration management. In addition, mostly individual aspects of reconfiguration are considered instead of exploiting the entire reconfiguration space at system and machine level. Therefore, in this paper we present reconfiguration management as a holistic problem. For this purpose we present the problem set up and show an overview of possible goals that can be achieved by reconfiguration management.